2019
DOI: 10.3382/ps/pez023
|View full text |Cite
|
Sign up to set email alerts
|

Animal-based welfare indicators of 4 slow-growing broiler genotypes for the approval in an animal welfare label program

Abstract: For broiler genotypes to be merchandized under the animal welfare label of the German Animal Welfare Federation, several animal-based welfare indicators with upper limits are listed in a criteria catalog. We compared the prevalence of animal-based welfare indicators in 4 slow-growing broiler genotypes [ Ranger Classic ( RC ), Ranger Gold ( RG ), Rowan Ranger ( RoR ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
6
15
0
Order By: Relevance
“…The plumage in approximately half of all chickens in the present study was considered slightly or moderately dirty, whereas in the other half it was without remarks. In previous studies on slower-growing hybrids, none of them performed under commercial rearing conditions however, and only one on birds with free-range access [15], the proportions of birds with clean plumage reported have been lower [15,43] as well as higher [42]. No birds were assessed as very dirty in the present study, in accordance with the aforementioned studies [42,43].…”
Section: Plumagesupporting
confidence: 90%
See 2 more Smart Citations
“…The plumage in approximately half of all chickens in the present study was considered slightly or moderately dirty, whereas in the other half it was without remarks. In previous studies on slower-growing hybrids, none of them performed under commercial rearing conditions however, and only one on birds with free-range access [15], the proportions of birds with clean plumage reported have been lower [15,43] as well as higher [42]. No birds were assessed as very dirty in the present study, in accordance with the aforementioned studies [42,43].…”
Section: Plumagesupporting
confidence: 90%
“…Mild signs of HB were observed in 13% of all chickens, whereas the remaining animals assessed had no signs of HB. Similar results were found in earlier studies on slower-growing hybrids, however these were reared under experimental conditions with [15,42] or without [43,44] winter-garden or outdoor access. The absence of moderate and severe HB lesions is in contrast to some earlier findings [42,43], but in agreement with others [44].…”
Section: Foot Pad Dermatitis and Hock Burnssupporting
confidence: 87%
See 1 more Smart Citation
“…Most authors reported a lower final body weight, poorer feed conversion efficiency, and better meat quality in freerange housing systems compared to conventional rearing (Bogosavljevic-Boslovic et al, 2012). Slow-growing genotypes are becoming popular in free-range production and organic chicken meat production due to some welfare problems of fast-growing broilers in conventional production (Hartcher and Lum, 2019;Louton, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The growth rate classification of the different lines was provided by the breeding companies. As for Aviagen strains, a previous study confirmed RC as fast-growing, RG as medium-growing, and RR as slow-growing [ 21 ]. For Hubbard lines, no comparative studies were available, but the breeder company ranking was applied as well (i.e., CY and M medium/fast growing and C slow growing).…”
Section: Methodsmentioning
confidence: 85%